Normative scores for the three factor eating questionnaire (TFEQ-R18) in a UK population-based cohort - Cara F. Ruggiero; Laura Kudlek; Julia Mueller; Simon J. Griffin; Stephen J. Sharp; Nick J. Wareham; Soren Brage; Nita G. Forouhi; Ken K. Ong; Amy Ahern (Appetite, 2026)

Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Cross-system transfer of fatty acids from aquatic insects supports terrestrial insectivore condition and reproductive success - Catrin F. Eden; Richard K. Broughton; Bart Donato; Chris M. Hewson; Caroline Isaksson; Stuart P. Sharp (Oecologia, 2025)
Cross-system fluxes of aquatic insects rich in omega-3 long-chain polyunsaturated fatty acids (ω-3 LC-PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may subsidise insectivorous vertebrates that are suffering due to terrestrial insect declines. The benefits of high ω-3 LC-PUFA diets, such as improved growth and immunocompetence, have previously been demonstrated for riparian insectivores. Understanding the potential for aquatic insects to benefit a range of species is necessary for informing land management practices. Using the spotted flycatcher ( Muscicapa striata ), a habitat-generalist, insectivorous bird as a model, we tested how blood plasma ω-3 LC-PUFA concentrations and the ratio of ω-6:ω-3 fatty acids were related to the body condition of 14 adults and 84 chicks in the wild. We measured how variation in ω-3 LC-PUFAs and ω-6:ω-3 was related to river proximity, to test whether they were related to aquatic insect availability. We assessed how these relationships may extend beyond the individual level by monitoring flying insect availability throughout two breeding seasons and testing its ability to predict reproductive success. EPA was positively correlated with body condition in chicks and adults and declined with distance from a river. Conversely, ω-6:ω-3 was negatively correlated with body condition and increased with distance from a river. Breeding success was positively correlated with aquatic insect availability, suggesting that access to a high ω-3 LC-PUFA diet has the potential to mitigate declines in generalist insectivores. Our results highlight how the maintenance or creation of high-quality freshwater habitats may be promoted in a conservation context for non-riparian species.

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

COVID-19 Pandemic Telemedicine Compared to Pre-pandemic In-person Delivery of the New Direction® Program for Weight Loss Success - H. Saroka; J. Schwartz; K. Sharp; J. Ponce; C. Hanson; M. Timmerman; M. Jackson (Journal of the Academy of Nutrition and Dietetics, 2024)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

The role of trade in pacific food security and nutrition - T.D. Brewer; N.L. Andrew; D. Abbott; R. Detenamo; E.N. Faaola; P.V. Gounder; N. Lal; K. Lui; A. Ravuvu; D. Sapalojang; M.K. Sharp; R.J. Sulu; et al. (Global Food Security, 2023)

Selective 2-desulfation of tetrasaccharide-repeating sulfated fucans during oligosaccharide production by mild acid hydrolysis - Seon Beom Kim; Marwa Farrag; Sushil K. Mishra; Sandeep K. Misra; Joshua S. Sharp; Robert J. Doerksen; Vitor H. Pomin (Carbohydrate Polymers, 2023)

Structural characterization and biological activity of an α-glucan from the mollusk Marcia hiantina (Lamarck, 1818) - Hoda Al. Ahmed; Bernadeth F. Ticar; Ian Black; Fakhri Mahdi; Anter A. Shami; Sandeep K. Misra; Christian Heiss; Jason J. Paris; Joshua S. Sharp; Parastoo Azadi; Vitor H. Pomin (Glycoconjugate Journal, 2023)

Exposure to global change and microplastics elicits an immune response in an endangered coral - Colleen B. Bove; Katharine Greene; Sharla Sugierski; Nicola G. Kriefall; Alexa K. Huzar; Annabel M. Hughes; Koty Sharp; Nicole D. Fogarty; Sarah W. Davies (Frontiers in Marine Science, 2023)
Global change is increasing seawater temperatures and decreasing oceanic pH, driving declines of coral reefs globally. Coral ecosystems are also impacted by local stressors, including microplastics, which are ubiquitous on reefs. While the independent effects of these global and local stressors are well-documented, their interactions remain less explored. Here, we examine the independent and combined effects of global change (ocean warming and acidification) and microplastics exposures on gene expression (GE) and microbial community composition in the endangered coral Acropora cervicornis . Nine genotypes were fragmented and maintained in one of four experimental treatments: 1) ambient conditions (ambient seawater, no microplastics; AMB); 2) microplastics treatment (ambient seawater, microplastics; MP); 3) global change conditions (warm and acidic conditions, no microplastics; OAW); and 4) multistressor treatment (warm and acidic conditions with microplastics; OAW+MP) for 22 days, after which corals were sampled for genome-wide GE profiling and ITS2 and 16S metabarcoding. Overall A. cervicornis GE responses to all treatments were subtle; however, corals in the multistressor treatment exhibited the strongest GE responses, and genes associated with innate immunity were overrepresented in this treatment. ITS2 analyses confirmed that all coral were associated with Symbiodinium ‘fitti’ and 16S analyses revealed similar microbiomes dominated by the bacterial associate Aquarickettsia , suggesting that these A. cervicornis fragments exhibited remarkably low variability in algal and bacterial community compositions. Future work should focus on functional differences across microbiomes, especially Aquarickettsia and viruses, in these responses. Overall, results suggest that when local stressors are coupled with global change, these interacting stressors present unique challenges to this endangered coral species.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Differential response to prey quorum signals indicates predatory specialization of myxobacteria and ability to predate Pseudomonas aeruginosa - Shukria Akbar; Kayleigh E. Phillips; Sandeep K. Misra; Joshua S. Sharp; D. Cole Stevens (Environmental Microbiology, 2022)
Summary Multiomic analysis of transcriptional and metabolic responses from the predatory myxobacteria Myxococcus xanthus and Cystobacter ferrugineus exposed to prey signalling molecules of the acylhomoserine lactone and quinolone quorum signalling classes provided insight into predatory specialization. Acylhomoserine lactone quorum signals elicited a general response from both myxobacteria. We suggest that this is likely due to the generalist predator lifestyles of myxobacteria and ubiquity of acylhomoserine lactone signals. We also provide data that indicates the core homoserine lactone moiety included in all acylhomoserine lactone scaffolds to be sufficient to induce this general response. Comparing both myxobacteria, unique transcriptional and metabolic responses were observed from Cystobacter ferrugineus exposed to the quinolone signal 2‐heptylquinolin‐4(1 H )‐one (HHQ) natively produced by Pseudomonas aeruginosa . We suggest that this unique response and ability to metabolize quinolone signals contribute to the superior predation of P. aeruginosa observed from C. ferrugineus . These results further demonstrate myxobacterial eavesdropping on prey signalling molecules and provide insight into how responses to exogenous signals might correlate with prey range of myxobacteria.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

COVID-19 and Pacific food system resilience: opportunities to build a robust response - Penny Farrell; Anne Marie Thow; Jillian Tutuo Wate; Nichol Nonga; Penina Vatucawaqa; Tom Brewer; Michael K. Sharp; Anna Farmery; Helen Trevena; Erica Reeve; Hampus Eriksson; Itziar Gonzalez; et al. (Food Security, 2020)

Development and molecular cytogenetic characterization of Thinopyrum bessarabicum introgression lines in hexaploid and tetraploid wheats - Amit K. Singh; Peng Zhang; Chongmei Dong; Jianbo Li; Smriti Singh; Richard M. Trethowan; Peter J. Sharp (Theoretical and Applied Genetics, 2020)

Self-reported health and survival in older patients diagnosed with multiple myeloma - Nadia A. Nabulsi; Ali Alobaidi; Brian Talon; Alemseged A. Asfaw; Jifang Zhou; Lisa K. Sharp; Karen Sweiss; Pritesh R. Patel; Naomi Y. Ko; Brian C.-H. Chiu; Gregory S. Calip (Cancer Causes & Control, 2020)

Compensated Hydroxyl Radical Protein Footprinting Measures Buffer and Excipient Effects on Conformation and Aggregation in an Adalimumab Biosimilar - Sandeep K. Misra; Ron Orlando; Scot R. Weinberger; Joshua S. Sharp (The AAPS Journal, 2019)

Larval influx of Diadema antillarum to the Florida Keys linked to passage of a Tortugas Eddy - Colette J. Feehan; William C. Sharp; Travis N. Miles; Michael S. Brown; Diane K. Adams (Coral Reefs, 2019)

Peptide Inhibitor of Complement C1 (PIC1) Inhibits Growth of Pathogenic Bacteria - Pamela S. Hair; Magdielis Gregory Rivera; Adrianne I. Enos; Susan E. Pearsall; Julia A. Sharp; Nazita Yousefieh; Frank A. Lattanzio; Neel K. Krishna; Kenji M. Cunnion (International Journal of Peptide Research and Therapeutics, 2019)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Critical Review on the Public Health Impact of Norovirus Contamination in Shellfish and the Environment: A UK Perspective - Francis Hassard; Jasmine H. Sharp; Helen Taft; Lewis LeVay; John P. Harris; James E. McDonald; Karen Tuson; James Wilson; David L. Jones; Shelagh K. Malham (Food and Environmental Virology, 2017)

The carbon fertilization effect over a century of anthropogenic CO 2 emissions: higher intracellular CO 2 and more drought resistance among invasive and native grass species contrasts with increased water use efficiency for woody plants in the US Southwest - Brandon L. Drake; David T. Hanson; Timothy K. Lowrey; Zachary D. Sharp (Global Change Biology, 2017)
From 1890 to 2015, anthropogenic carbon dioxide emissions have increased atmospheric CO 2 concentrations from 270 to 400 mol mol −1 . The effect of increased carbon emissions on plant growth and reproduction has been the subject of study of free‐air CO 2 enrichment ( FACE ) experiments. These experiments have found (i) an increase in internal CO 2 partial pressure ( c i ) alongside acclimation of photosynthetic capacity, (ii) variable decreases in stomatal conductance, and (iii) that increases in yield do not increase commensurate with CO 2 concentrations. Our data set, which includes a 115‐year‐long selection of grasses collected in New Mexico since 1892, is consistent with an increased c i as a response to historical CO 2 increase in the atmosphere, with invasive species showing the largest increase. Comparison with Palmer Drought Sensitivity Index ( PDSI ) for New Mexico indicates a moderate correlation with Δ 13 C ( r 2 = 0.32, P r 2 = 0.00, P = 0.91) after 1950. These results indicate that increased c i may have conferred some drought resistance to these grasses through increased availability of CO 2 in the event of reduced stomatal conductance in response to short‐term water shortage. Comparison with C 3 trees from arid environments ( Pinus longaeva and Pinus edulis in the US Southwest) as well as from wetter environments ( Bromus and Poa grasses in New Mexico) suggests differing responses based on environment; arid environments in New Mexico see increased intrinsic water use efficiency ( WUE ) in response to historic elevated CO 2 while wetter environments see increased c i . This study suggests that (i) the observed increases in c i in FACE experiments are consistent with historical CO 2 increases and (ii) the CO 2 increase influences plant sensitivity to water shortage, through either increased WUE or c i in arid and wet environments, respectively.

Fertilization limitation of Diadema antillarum on coral reefs in the Florida Keys - Colette J. Feehan; Michael S. Brown; William C. Sharp; Jean‐Sébastien Lauzon‐Guay; Diane K. Adams (Ecology, 2016)
Mass mortality of the sea urchin Diadema antillarum due to disease outbreaks in 1983 and 1991 decimated populations in the Florida Keys, and they have yet to recover. Here, we use a coupled advection–diffusion and fertilization–kinetics model to test the hypothesis that these populations are fertilization limited. We found that fertilization success was ≥ 96% prior to the first disease outbreak, decreased substantially following recurrent disease to 3%, and has since remained low. By investigating the combined effects of physical factors (population spatial extent and current velocity) and sea urchin behavior (aggregation) on density‐dependent fertilization success, we show that fertilization success at a given density increases with increasing population spatial extent and decreasing current velocity, and is greater under simulated aggregation behavior of D. antillarum . However, at present population densities, the increase in fertilization success due to aggregation is D. antillarum restocking program to obtain reproductively viable populations.

Understanding Climate Adaptation on Public Lands in the Upper Midwest: Implications for Monitoring and Tracking Progress - Christine M. Anhalt-Depies; Tricia Gorby Knoot; Adena R. Rissman; Anthony K. Sharp; Karl J. Martin (Environmental Management, 2016)

Peristalsis with Oscillating Flow Resistance: A Mechanism for Periarterial Clearance of Amyloid Beta from the Brain - M. Keith Sharp; Alexandra K. Diem; Roy O. Weller; Roxana O. Carare (Annals of Biomedical Engineering, 2016)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

A simple temperature-based model predicts the upper latitudinal limit of the temperate coral Astrangia poculata - J. L. Dimond; A. H. Kerwin; R. Rotjan; K. Sharp; F. J. Stewart; D. J. Thornhill (Coral Reefs, 2013)

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Population pharmacokinetic modeling of tramadol and its O-desmethyl metabolite in plasma and breast milk - Sam Salman; Sherwin K. B. Sy; Kenneth F. Ilett; Madhu Page-Sharp; Michael J. Paech (European Journal of Clinical Pharmacology, 2011)

Spatial movement optimization in Amazonian Eciton burchellii army ants - S. K. Willson; R. Sharp; I. P. Ramler; A. Sen (Insectes Sociaux, 2011)

A novel approach identified the FOLR1 gene, a putative regulator of milk protein synthesis - Karensa K. Menzies; Christophe Lefèvre; Julie A. Sharp; Keith L. Macmillan; Paul A. Sheehy; Kevin R. Nicholas (Mammalian Genome, 2009)

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

Identification and imaging of soil and soil-pile deformation in the presence of liquefaction - M. Zeghal; P. V. Kallou; C. Oskay; T. Abdoun; M. K. Sharp (Earthquake Engineering and Engineering Vibration, 2006)

Starch branching enzyme IIb in wheat is expressed at low levels in the endosperm compared to other cereals and encoded at a non-syntenic locus - Ahmed Regina; Behjat Kosar-Hashemi; Zhongyi Li; Andrew Pedler; Yasuhiko Mukai; Maki Yamamoto; Kevin Gale; Peter J. Sharp; Matthew K. Morell; Sadequr Rahman (Planta, 2005)

Physical modeling and visualization of soil liquefaction under high confining stress - Lenart González; Tarek Abdoun; Mourad Zeghal; Vivian Kallou; Michael K. Sharp (Earthquake Engineering and Engineering Vibration, 2005)

Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort - F. Denk; M. E. Walton; K. A. Jennings; T. Sharp; M. F. S. Rushworth; D. M. Bannerman (Psychopharmacology, 2005)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Metazoan parasites of yellowtail kingfish, Seriola lalandi lalandi , in New Zealand: Prevalence, intensity, and site preference - N. J. Sharp; C. W. Poortenaar; B. K. Diggles; T. J. Willis (New Zealand Journal of Marine and Freshwater Research, 2003)
The prevalence and intensity of metazoan ectoparasites on the skin and gills of kingfish, Seriola lalandi lalandi (Carangidae), collected from White Island (n = 32), Ranfurly Banks (n = 7), and Three Kings Islands (n = 7), is reported. Kingfish were host to two monogenean and four copepod ectoparasite species, Benedenia seriolae, Zeuxapta seriolae, Caligus lalandei, Caligus aesopus, Neobrachiella spp., and Lernanthropus spp., respectively. B. seriolae and C. lalandei infect the skin, whereas the remaining parasites were located on the gills. All parasites exhibited considerable variability in the prevalence and intensity of infection. A few kingfish were completely devoid of C. aesopus, Neobrachiella spp., and/or Lernanthropus spp., whereas others were infected by moderate numbers of these species. However, all kingfish were infected by B. seriolae and Z. seriolae . Therefore, it appears that acclimation of wild kingfish from the east coast of New Zealand's North Island into captivity will lead to the transfer of both B. seriolae and Z. seriolae , and that effective quarantine measures will be required to avoid introducing these parasites into broodstock systems. The site preferences of B. seriolae, Z. seriolae , and C. aesopus were also investigated. B. seriolae exhibited a preference for attachment on the lateral surfaces of the skin behind the dorsal fin, but forward of the anal fin. Z. seriolae displayed a preference for attachment on gill arches 2 and 3, particularly in gill filaments located in the upper regions of the buccal cavity. C. aesopus most commonly occurred on the gill arch.

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Effect of antidepressant drugs on dopamine D 1 and D 2 receptor expression and dopamine release in the nucleus accumbens of the rat - K. Ainsworth; S. E. Smith; T. S. C. Zetterström; Q. Pei; M. Franklin; T. Sharp (Psychopharmacology, 1998)

Infection of specific-pathogen free lambs with a herpesvirus isolated from pulmonary adenomatosis - F. M. M. Scott; J. M. Sharp; K. W. Angus; E. W. Gray (Archives of Virology, 1984)

Rapid transmission of sheep pulmonary adenomatosis (jaagsiekte) in young lambs - J. M. Sharp; K. W. Angus; E. W. Gray; F. M. M. Scott (Archives of Virology, 1983)